Unravelling the Therapeutic Potential of Botanicals Against Chronic Obstructive Pulmonary Disease (COPD): Molecular Insights and Future Perspectives - Mitra, Sicon; Anand, Uttpal; Ghorai, Mimosa; Vellingiri, Balachandar; Jha, Niraj Kumar; Behl, Tapan; Kumar, Manoj; Radha; Shekhawat, Mahipal S.; Proćków, Jarosław; Dey, Abhijit (Frontiers in Pharmacology, 2022)
Graphical Abstract